Utilização de óleo de soja associado ao óleo de linhaça em dietas para frangos de corte - Amorim, Bruno Guimarães (2017)
The objective of this study was to evaluate the effects of the partial and total replacement, in the broiler chicken diet, of soybean oil for a commercial oil consisting, predominantly, of omega 3 (n-3) polyunsaturated fatty acids (PUFA) over performance, carcass yield, fatty acid profile and physicochemical traits of the meat. One hundred and eighty male Cobb-500 chicks, of one day of age, were distributed in a completely randomized design with three treatments and six replicates. The treatments were as follows: T1 = 0% commercial oil and 2.55% soybean oil; T2 = 2% commercial oil and 0.85% soybean oil; and T3 = 3% commercial oil and 0% soybean oil. The experimental period was of 21 days, beginning the supplementation of the experimental diets when the birds completed 22 days of age. There were no significant differences between treatments regarding weight gain, feed intake, feed conversion, carcass yield, breast, thigh and abdominal fat yield and total lipid content in breast and thigh. Concerning the fatty acid profile in the breast, a quadratic response of the deposition of palmitic acid, linear reduction of the deposition of linoleic (LA) and gama-linolenic acids, and a linear increase of the deposition of alpha-linolenic (ALA), eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids was verified with the increase in the level of commercial oil supplementation. The supplementation led to a linear reduction of LA deposition and a quadratic response in the deposition of ALA, EPA and DHA in the thigh. Regarding the physicochemical traits of the chicken breast, pH, luminosity (L*) and yellow content (b*) were not influenced by the replacement of soybean oil for commercial oil. Meanwhile, the red content (a*) responded to the supplementation in a quadratic manner. In conclusion, the evaluated levels of commercial oil did not influence production or the physicochemical traits of breast and thigh. However, the use of commercial oil resulted in higher deposition of n-3 PUFAs and lower deposition of omega 6 (n-6) PUFAs in the evaluated meat cuts, which may contribute to health promotion in humans that consume these products.